The role of Ethical Leadership in nurses\' psychological empowerment - mohammad moosavi jed; siroos ghanbari; khalil zandi; bita rafeizad; hamed seifpanahi; maryam noradini (Tehran University of Medical Sciences, 2015)
Abstract: Background: According to reports, the nurses frequently and directly are faced with the deaths, suffering and pain, thus a major mechanism for administrators is empowering of staff. With this approach, the object of study was examining the role of ethical leadership at promote nurses' psychological empowerment. Material and Methods: Considering the purpose of this study, it was applied & considering the data collection methods, it was descriptive -analytical. Statistical population was nurses in working in Sanandaj public hospitals (410 people) and 148 subjects were selected using random sampling. Data gathering tools were two questionnaires: Ethical Leadership (Salehnia: 2012) and psychological empowerment Questionnaire (Wooten & Cameron, 1998). Data analysis was performed by SPSS (Version 16) and Confirmatory Factor Analysis, Pearson correlation test and Multiple Regression (Method: Enter). Results: Results showed that the items of questionnaires can be reduced to the fundamental dimensions. Results also showed that there was a significant relationship between ethical leadership and psychological empowerment. Finally, it was found that components of Pattern and Pragmatism are predictive of psychological empowerment. Conclusion: According to study findings, hospital Administrators can by display appropriate ethical behaviors and efforts to strengthen interpersonal relationships and encourage such behaviors among members provide Contexts improving nurses' Psychological Empowerment